Planting stories : the life of librarian and storyteller Pura Belpre - Denise, Anika (Harper, an imprint of HarperCollinsPublishers, 2019)
Nonfiction picture book about the life and legacy of Pura Belpre, the first Puerto Rican librarian in New York City.